Environmental Resilience and Food Law Agrobiodiversity and Agroecology. - Steier, Gabriela; Cianci, Alberto Giulio (Milton : CRC Press LLC, 2019)
Agrobiodiversity and agroecology go hand-in-hand in promoting environmental resilience in international food systems as well as climate change resilient food policy. This book contextualizes how various legal frameworks address agrobiodiversity and agroecology around the globe and makes it accessible for audiences of students, practitioners, educators, and scholars. Some chapters focus on the legal regulation of agroecology from a food law perspective. Others are geared toward providing regulators, lawmakers and attorneys with the scientific and policy background of those concepts, so that they are equipped in the field of food law in everyday practice and policy. Climate change dimensions of the issues are woven throughout the book.
5.3 Case study: Pygmies and bushmeat hunting and consumption in the Congo Basin5.3.1 Overview; 5.3.2 Biodiversity in the Congo Basin; 5.3.3 Bushmeat consumption in the Congo Basin; 5.3.4 International bushmeat trade; 5.3.5 Effects of bushmeat consumption; 5.3.5.1 Wildlife depletion; 5.3.5.2 Disease risk; 5.3.5.3 Ineffective legal systems; 5.3.5.4 A way forward: the importance of indigenous values in conservation efforts; 5.4 Case study: resource diversification and collaborative action by the Mbororo pastoralists in the North-West Region of Cameroon; 5.4.1 Overview
Description based upon print version of record.
5.4.2 The Mbororos and agrobiodiversity
OCLC-licensed vendor bibliographic record.
Keywords: Food law and legislation; Agrobiodiversity conservation -- Law and legislation; Sustainable agriculture -- Law and legislation; SCIENCE / Life Sciences / General